Synergistic antitumor activity of gemcitabine combined with triptolide in pancreatic cancer cells - QIAO, ZHIXIN (Oncol Lett, 2016)
Pancreatic cancer is a fatal human malignancy associated with an exceptionally poor prognosis. Novel therapeutic strategies are urgently required to treat this disease. In addition to immunosuppressive activity, triptolide possesses strong antitumor activity and synergistically enhances the antitumor activities of conventional chemotherapeutic drugs in preclinical models of pancreatic cancer. The present study investigated the antitumor effects of triptolide in pancreatic cancer cells, either in combination with gemcitabine, or alone. The pancreatic cancer BxPC-3 and PANC-1 cell lines were treated with triptolide, which resulted in time- and dose-dependent growth arrest. When incorporated into a sequential schedule, triptolide synergistically increased gemcitabine-induced cell growth inhibition and apoptosis, in addition to the cooperative regulation of B-cell lymphoma 2 family proteins and loss of mitochondrial membrane potential. Furthermore, triptolide enhanced gemcitabine-induced S phase arrest and DNA double-strand breaks, possibly through checkpoint kinase 1 suppression. The results of the present study suggest that triptolide has therapeutic potential for the treatment of pancreatic cancer, particularly when administered in combination with gemcitabine.